Fungal Endophyte-Mediated Crop Improvement: The Way Ahead - Chitnis, Vijaya R.; Suryanarayanan, Trichur S.; Nataraja, Karaba N.; Prasad, S. Rajendra; Oelmüller, Ralf; Shaanker, R. Uma (Frontiers in Plant Science, 2020)
Endophytes are non-disease causing microbes (bacteria and fungi) surviving in living tissues of plants. Their intimate association and possible coevolution with their plant partners have resulted in them contributing to an array of plant growth benefits ranging from enhanced growth and biomass accumulation, tolerance to abiotic and biotic stresses and in nutrient acquisition. The last couple of decades have witnessed a burgeoning literature on the role of endophytes in regulating plant growth and development and their adaptation to abiotic and biotic stresses. Though the underlying mechanisms of plant-endophyte interactions are far from clear, several studies have raised the hope of their potential application in agriculture, especially in mitigating abiotic and biotic stresses. The use of endophytes is envisaged as a route to reduce the production cost and burden on the environment by lessening the dependence on breeding for crop improvement and agrochemicals. Unfortunately, save a few well documented examples of their use, a little of these insights has been translated into actual agricultural applications. Here, we reflect on this paucity and elaborate on some of the important bottlenecks that might stand in way of fully realizing the potential that endophytes hold for crop improvement. We stress the need to study various facets of the endophyte-plant association for their gainful application in agriculture.